Relationship between vertical jump height and swimming start performance before and after an altitude training camp - Garcia-Ramos, A.; Padial, P.; De La Fuente, B.; Arguelles-Cienfuegos, J.; Bonitch-Gongora, J.; Feriche, B. (The Journal of Strength and Conditioning Research, 2016)
This study aimed (a) to analyze the development in the squat jump height and swimming start performance after an altitude training camp, (b) to correlate the jump height and swimming start performance before and after the altitude training period, and (c) to correlate the percent change in the squat jump height with the percent change in swimming start performance. Fifteen elite male swimmers from the Spanish Junior National Team (17.1 ± 0.8 years) were tested before and after a 17-day training camp at moderate altitude. The height reached in the squat jump exercise with additional loads of 0, 25, 50, 75, and 100% of swimmers' pretest body weight and swimming start performance (time to 5, 10, and 15 m) were the dependent variables analyzed. Significant increases in the jump height (p = 0.05; effect size [ES]: 0.35-0.48) and swimming start performance (p < 0.01; ES: 0.48-0.52) after the training period were observed. The start time had similar correlations with the jump height before training (r = -0.56 to -0.77) and after training (r = -0.50 to -0.71). The change in the squat jump height was inversely correlated with the change in the start time at 5 m (r = -0.47), 10 m (r = -0.73), and 15 m (r = -0.62). These results suggest that altitude training can be suitable to enhance explosive performance. The correlations obtained between the squat jump height and start time in the raw and change scores confirm the relevance of having high levels of lower-body muscular power to optimize swimming start performance.